The Relationship Between Self-Control and Multidimensional Student Engagement in Learning Among Junior High School Students - Hadis, Nur Athirah; Akmal, Nur; Rasyid, Nurfajriyanti (Universitas Muhammadiyah Yogyakarta, 2025)
Low student engagement in learning remains a serious problem in junior high school education, particularly in Indonesia. Initial survey data from 36 students showed that 52.7% had skipped school without permission, 50% were frequently late, and 75% felt unmotivated to learn. This condition underscores the importance of research on psychological factors that contribute to increased student engagement. This study aims to examine the relationship between self-control and student engagement, which includes four dimensions: agentic, behavioral, emotional, and cognitive, based on the framework proposed by Fredricks et al. (2004) and further developed by Reeve and Tseng (2011). The method employed was a quantitative correlational design, with 207 students aged 12–16 years selected through convenience sampling. The instruments used were the Student Engagement Scale (20 items, ω = .876) and the Self-Control Scale (20 items, ω = .844). Analysis using Pearson's Product-Moment correlation showed a significant positive relationship between self-control and student learning engagement (r = 0.466, p < 0.001). The highest correlation was found in the behavioral dimension, followed by emotional, cognitive, and agentic dimensions. Additional analysis revealed differences based on gender and grade level: female and seventh-grade students had higher self-control and learning engagement than male and eighth-grade students. The novelty of this study lies in testing a multidimensional model of student engagement simultaneously, with self-control as the primary predictor, in the context of Indonesian junior high school students. This topic has been rarely researched. Practically, the results of this study recommend implementing self-control training through character-based activities and self-reflection in school, as well as consistent parenting support at home, to continually increase student learning engagement.